Literature Review: Efektivitas Kinesio Taping dan Exercise terhadap Intensitas Nyeri pada Pasien Carpal Tunnel Syndrome - Muhammad Rifqi Haikal; Fathia Arsyiana; Didik Dwi Sanyoto (Homeostasis, 2022)
Abstract: Pain is one of the symptoms that are often found in patients with Carpal Tunnel Syndrome (CTS) which can cause nuisance and discomfort to the patient. Kinesio Tape (KT) is a medical rehabilitation through gate control theory mechanism and elevates soft tissue that compresses the median nerve. The purpose of this literature review is to determine the effect of KT on reducing pain intensity in CTS patients, and to determine the effect of KT combined with exercise on the pain intensity of CTS patients. This study was done by analyzing library sources from several medical journal databases, namely Google Scholar, PubMed, and Science Direct. Based on the search process, 10 journals were found that were used as topics in this review. The results of this paper indicate the effect of KT on reducing pain intensity, whether combined with exercise or not. Keywords : carpal tunnel syndrome, pain, kinesio tape, exercise Abstrak: Nyeri merupakan salah satu gejala yang sering ditemukan pada pasien Carpal Tunnel Syndrome (CTS) yang dapat menyebabkan gangguan dan ketidaknyamanan pada pasien. Kinesio Tape (KT) merupakan rehabilitasi medis melalui mekanisme gate control theory dan mengangkat jaringan lunak yang menekan nervus medianus. Tujuan literature review ini untuk mengetahui pengaruh KT tehadap penurunan intensitas nyeri pada pasien CTS, dan mengetahui pengaruh KT yang dikombinasikan dengan exercise terhadap intensitas nyeri pasien CTS. Penulisan ini dilakukan dengan menganalisis sumber pustaka dari beberapa database jurnal kedokteran yaitu google scholar, PubMed, dan Science Direct. Berdasarkan proses pencarian, didapatkan 10 jurnal yang dijadikan bahasan topik pada literatur ini. Hasil penulisan ini menunjukkan adanya pengaruh KT pada penurunan intensitas nyeri baik dikombinasikan dengan exercise ataupun tidak. Kata-kata kunci: carpal tunnel syndrome, pain, kinesio tape, exercise